An atomic level transition metal iridium doped indium oxide ethanol gas sensor
Patent Information
- Application Number
- CN202511223336.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-08-29
AI Technical Summary
[0006]本发明为解决传统掺杂方式中原子易团聚、材料内部掺杂原子利用率不高的问题,进而提出一种原子级过渡金属铱掺杂氧化铟的乙醇气体传感器
本发明通过沉淀法,以硝酸铟纳米颗粒为铟源制备了具有均匀分散原子级铱掺杂氧化材料。不同于传统掺杂手段存在掺杂原子团聚、材料内部掺杂原子利用率低的缺陷,该方法获得的高利用率和大量的活性位点能显著提高材料的气敏性能。
Smart Images

Figure CN120948565B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an ethanol gas sensor, belonging to the field of gas sensor technology. Background Technology
[0002] Gas sensors are invaluable in disease diagnosis, environmental monitoring, food safety, and extreme environments (such as polar regions, deep seas, and outer space). However, traditional devices still face challenges such as low sensitivity, slow response, baseline drift, and high-temperature operation. In recent years, semiconductor resistive sensors have become a research hotspot due to their advantages of high sensitivity, low cost, and easy integration. The performance of the sensitive material directly determines its final performance. Single-atom catalysts, with their atomically dispersed metal sites, can achieve maximum utilization of precious metals, reduce reaction energy barriers, and significantly improve selectivity, and are considered a new approach to overcome the bottlenecks of traditional nanomaterials. Their catalytic behavior is highly similar to the gas-solid interface reaction in gas sensing processes, thus promising to achieve high-sensitivity, low-temperature, and rapid detection of trace gases by enhancing gas adsorption-activation-electron transfer efficiency.
[0003] Indium oxide (IO), a typical environmentally friendly n-type semiconductor metal oxide material, has attracted much attention in related fields due to its rapid detection response, low detection cost, and convenient operation process. Its crystal structure is cubic ferromanganese oxide (CFI) with a band gap of approximately 2.8–3.6 eV. It also possesses high carrier mobility (~10–160 cm² / V·s) and excellent chemical stability, making it an ideal candidate material to replace traditional heavy metal oxides (such as SnO₂ and ZnO).
[0004] In industry, ethanol is a commonly used raw material. Its vapor is flammable and explosive; real-time concentration monitoring can provide early warning of dangers, prevent explosions, and ensure production safety. In environmental monitoring, large amounts of ethanol emissions participate in atmospheric reactions, affecting air quality; detection can assist in the formulation of environmental protection policies. In the medical field, detection can ensure air quality in the workplace and prevent harm caused by excessively high ethanol concentrations. Ethanol gas detection plays a crucial role in ensuring industrial safety, environmental protection, and healthcare.
[0005] In fact, research on ethanol gas sensors has been continuously deepening over the past few years, and semiconductor gas sensors (zinc oxide, ferric oxide, tungsten oxide, etc.) and hybrid potential gas sensors (zinc oxide / graphene and bismuth tungstate / reduced graphene oxide, etc.) have been developed. However, traditional ethanol metal oxide semiconductor gas sensors suffer from drawbacks such as long response time, high cost, non-specific selectivity, insufficient sensitivity, and a need to reduce the minimum detection limit. Therefore, it is crucial to propose an ethanol gas sensor with single-atom doped metal oxide semiconductor nanomaterials to address these issues. Summary of the Invention
[0006] To address the problems of easy agglomeration of atoms and low utilization rate of doped atoms in traditional doping methods, this invention proposes an atomic-level transition metal iridium-doped indium oxide ethanol gas sensor.
[0007] The technical solution adopted by the present invention to solve the above problems is as follows: The present invention includes a ceramic tube coated with iridium-doped indium oxide material, and an alloy heating wire is provided inside the ceramic tube, with gold electrodes connected to both ends of the alloy heating wire.
[0008] Furthermore, the ceramic tube is an Al2O3 ceramic tube, and the alloy heating wire is a Ni-Gr alloy heating wire.
[0009] Furthermore, the preparation method of iridium-doped indium oxide material is as follows: Step 1: Weigh out indium nitrate; Step 2: Dissolve indium nitrate in a mixed solution of deionized water and ethanol, stir continuously and add ammonia water to obtain a suspension; Step 3: Stir the suspension obtained in Step 2 under heating conditions; Step 4: After washing and drying the white solid obtained from the reaction, transfer it to a muffle furnace for calcination to obtain indium oxide solid powder; Step 5: Weigh out indium oxide and chloroiridic acid for later use; Step 6: Dissolve the weighed indium oxide and chloroiridium acid in deionized water and stir under heating conditions; Step 7: After washing and drying the white solid obtained from the reaction, transfer it to a muffle furnace for calcination to obtain iridium-doped indium oxide solid powder.
[0010] Furthermore, the mass of indium nitrate weighed in step 1 is 5~15g.
[0011] Furthermore, in step 2, the volume of deionized water is 10 mL to 100 mL, the volume of ethanol is 100 to 200 mL, and the volume of ammonia is 10 to 100 mL.
[0012] Furthermore, in step 3, the heating temperature is 10~150℃, and the stirring time is no less than 5 hours.
[0013] Furthermore, in step 4, the working temperature of the muffle furnace is 400 ℃~600 ℃, the working time is not less than 1 h, and the heating rate is 2~10 ℃ / min.
[0014] Furthermore, in step 5, the mass ratio of indium nitrate to chloroiridium acid is 1:(0.1~1).
[0015] Furthermore, in step 6, the heating temperature is 10~150℃, and the stirring time is no less than 10 hours.
[0016] Furthermore, in step 7, the working temperature of the muffle furnace is 200 ℃~500 ℃, the working time is not less than 3 h, and the heating rate is 2~10 ℃ / min.
[0017] The beneficial effects of this invention are as follows: This invention employs a precipitation method, using indium nitrate nanoparticles as the indium source, to successfully prepare an atomically uniformly dispersed iridium-doped oxide material, overcoming the drawbacks of traditional doping methods such as easy agglomeration of atoms and low utilization rate of doped atoms within the material. Iridium doping not only increases the number of oxygen vacancies in the material but also enhances its oxygen adsorption capacity. Therefore, with its high utilization rate and abundant active sites, the gas-sensing performance of the material is significantly improved, enabling the preparation of rapid, specific, efficient, stable, non-toxic, and low-cost gas detection materials. In some test examples of this invention, the ethanol gas sensor prepared using the gas-sensing material of this invention achieved a response value of 75 for 100 ppm ethanol at 220°C.
[0018] The side-heated ethanol gas sensor based on single-atom iridium-doped indium oxide nanomaterial prepared in this invention has the following advantages: This invention utilizes a precipitation method to prepare a uniformly dispersed, atomically-level iridium-doped oxide material using indium nitrate nanoparticles as the indium source. Unlike traditional doping methods that suffer from dopant agglomeration and low utilization of dopant atoms within the material, this method achieves high utilization and a large number of active sites, significantly improving the gas-sensing properties of the material.
[0019] The nano-sensitive material prepared by this invention has the advantages of good repeatability, short response time, high selectivity and sensitivity, and the detection limit of the sensor can reach the ppm level, enabling long-term and stable use. The side-heated ethanol gas sensor made of single-atom iridium-doped indium oxide nanomaterial prepared by this invention has a simple preparation process, low material cost, and a green and environmentally friendly synthesis route, making it suitable for industrial production. Attached Figure Description
[0020] Figure 1 (a) is a schematic diagram of the planar structure of the iridium-doped indium oxide nanosensitive material-based side-heated ethanol gas sensor prepared in this invention; Figure 1 (b) is a SEM image of the iridium-doped indium oxide nanosensor material prepared in this invention; Figure 1 (c) is a diagram showing the iridium element distribution of the iridium-doped indium oxide nanosensitive material prepared in this invention; Figure 2 (a) is a TEM image of the iridium-doped indium oxide nanosensitive material prepared in this invention; Figure 2(b) is a STEM image of the iridium-doped indium oxide nanosensor material prepared in this invention; Figure 2 (c) is an HRTEM image of the iridium-doped indium oxide nanosensor material prepared in this invention; Figure 2 (d) are the XRD patterns of the iridium-doped indium oxide nanosensitive material (example) and the indium oxide nanosensitive material (comparative example) prepared in this invention; Figure 3 This is a selectivity chart of 100 ppm for different gases at 220°C for the comparative examples and embodiments described in this invention. Figure 4 These are the response curves of the comparative example and the embodiment to 100 ppm ethanol gas at 120 ℃-280 ℃, respectively. Figure 5 The concentration gradient of 1 ppm to 500 ppm ethanol in an atmosphere measured at 220 °C for the comparative and examples. Figure 6 The example shows the response recovery time curve of 100 ppm ethanol gas at 220 °C. Figure 7 This is a long-term stability graph of the comparative example and the embodiment measured at 220°C for 30 days; Figure 8 (a) is a schematic diagram showing the adsorption of oxygen to the point that the OO bonds in the comparative example and the embodiment break; Figure 8 (b) is a schematic diagram of the optimized structure of the proportions and embodiments; Figure 8 (c) Schematic diagram of the adsorption energy of oxygen, the binding energy of O, and the dissociation energy of oxygen; Figure 8 (d) shows the net spin density of *O at an isosurface value of 0.005 e Å. 3 Schematic diagram; Figure 1 In the middle, 1-gold electrode, 2-ceramic tube, 3-alloy heating wire.
[0021] Example An atomically-level transition metal iridium-doped indium oxide ethanol gas sensor includes a ceramic tube and a hexagonal socket. The ceramic tube structure consists of a tubular sensing element and four electrode pins, which are soldered to the hexagonal socket. Additionally, a nickel-chromium alloy coil passes through the tubular sensing element and is soldered to two other terminals of the hexagonal socket. The tubular sensing element is made of alumina (Al₂O₃)-based ceramic, and gold electrodes are located at both ends of the tubular sensing element.
[0022] Comparative example: The fabrication process of indium oxide nanomaterials for a heated ethanol gas sensor is as follows: Step 1. Preparation of indium oxide solid: Mix 12.2 g indium nitrate, 50 mL deionized water, and 140 mL ethanol, and stir thoroughly until dissolved. Then add 35 mL ammonia and 110 mL ethanol to the mixture; wash the resulting product alternately with water and anhydrous ethanol by centrifugation to obtain a white solid; Step 2. Preparation of indium oxide powder: The solid obtained in Step 1 was dried at 80℃ for 24h, then heated to 500℃ in a muffle furnace at a rate of 2℃ / min and held for 3h, and then cooled naturally to obtain indium oxide powder; Step 3. Preparation of indium oxide nanomaterial-based heated ethanol gas sensor: After the indium oxide nanomaterial is taken out, it is made into a suspension with ethanol and uniformly coated on the tubular sensing element at room temperature. Then, it is heated to 200 °C at a rate of 2 °C / min and calcined again for 2 h. The nickel-chromium alloy coil is inserted into the tubular sensing element after the above treatment, and then spot-welded to a hexagonal tube base. It is then aged for 3-5 days using an aging bench to obtain the heated ethanol gas sensor based on indium oxide nanomaterial.
[0023] Example: The prepared iridium-doped indium oxide nanomaterials were used to fabricate a side-heated ethanol gas sensor. The specific fabrication process is as follows: Step 1. Preparation of solid indium oxide: Same as the comparative example.
[0024] Step 2. Preparation of indium oxide powder: Same as the comparative example.
[0025] Step 3. Preparation of iridium-doped indium oxide: Take 1 g of indium oxide powder and 0.32 g of chloroiridium acid and dilute with deionized water to 50 mL. Then stir at 50 °C for 12 h. Wash the resulting precipitate with deionized water. Dry the resulting solid at 80 °C for 24 h, then heat it to 300 °C in a muffle furnace at a rate of 2 °C / min and hold for 3 h, then allow it to cool naturally to obtain iridium-doped indium oxide powder.
[0026] Step 4. Fabrication of a side-heated ethanol gas sensor using iridium-doped indium oxide nanomaterials: Same as the comparative example.
[0027] The indirect-heated sensor was connected to a Fluke multimeter signal tester via a clip. The sensors prepared in the comparative example and the embodiment were placed in air and 100 ppm ethanol atmospheres respectively to test the resistance signal.
[0028] SEM images of the iridium-doped indium oxide nanomaterials prepared in this invention are shown below. Figure 1 As shown in (b), by Figure 1 (b) As shown in the figure, the prepared iridium-doped indium oxide nanosensitive material is a uniformly sized granular nanosensitive material; the iridium elemental distribution diagram of the iridium-doped indium oxide nanosensitive material prepared in this invention is as follows. Figure 1 As shown in (c), the image shows that the iridium element is uniformly dispersed in the material.
[0029] Figure 2 Figure (a) shows an example where the prepared iridium-doped indium oxide sensitive material is composed of uniform nanoparticles with no obvious agglomeration and good dispersibility; Figure (b) shows an example where the prepared iridium-doped indium oxide nanosensitive material is a STEM image. As can be seen from the figure, iridium atoms are highly dispersed in the form of single atoms and uniformly loaded on the surface of the indium oxide support. Figure 2 (c) shows the HRTEM image of the prepared iridium-doped indium oxide nanosensitive material in the example. The image shows clear lattice fringes, which confirms the crystal structure of the indium oxide matrix. Figure 2 As shown in (d), the XRD images of the prepared comparative examples and embodiments are shown in the figure. It can be seen from the figure that the comparative examples and embodiments are completely compared with the indium oxide card PDF#06-0416.
[0030] The comparison graph of the response values of the comparative examples and embodiments to 100 ppm of different gases at 220°C is shown below. Figure 3 As shown. From Figure 3 As can be seen from the examples, the examples have good selectivity for 100 ppm ethanol.
[0031] The sensitivity of the comparative examples and embodiments to testing at 100 ppm ethanol atmosphere at temperatures ranging from 120 °C to 280 °C is as follows: Figure 4 As shown.
[0032] The concentration gradient curves of ethanol at 220 °C for the comparative examples and the actual examples, ranging from 1 ppm to 500 ppm, are shown below. Figure 5 As shown. Response value test method: First, place the sensor in the gas cylinder, and measure the resistance at this time using a meter connected to the sensor. This gives the sensor's resistance value in air, i.e., R. a Then, using a syringe, ethanol concentrations ranging from 1 ppm to 500 ppm are injected into the gas cylinder. The resistance value (R) of the sensor in ethanol at different concentrations is then measured. g According to the definition of sensitivity S, S = R a / Rg was used to calculate the sensor sensitivity at different concentrations. The graph shows that the sensor sensitivity increases with increasing ethanol concentration.
[0033] The response time curve of the example to ethanol at 220 °C is shown below. Figure 6 As shown, this material exhibits excellent response speed.
[0034] The long-term stability of the examples and comparative examples measured at 220°C for 30 days is as follows: Figure 7 As shown, this material exhibits good stability.
[0035] Comparative examples and optimized structures, such as Figure 8 (a) and 8(b) are shown on the left and in the middle, the configuration of oxygen facing the oxygen vacancy is shown. The oxygen adsorption energies of the two are similar, and the comparative example shows that the surface oxygen stability is slightly stronger. Considering the oxygen anion pathway reaction, the oxygen dissociation behavior of the comparative example and the example is studied. Figure 8 (a) and 8(b) (right side), it was found that the oxygen dissociation energy in the examples was much smaller than that in the comparative example, confirming that iridium is the key site promoting oxygen dissociation and can "activate" oxygen molecules. Furthermore, the binding energy of oxygen in the examples was more negative, indicating a stronger interaction with oxygen. Spin density calculations for the comparative and examples (Figure 8(d)) show that the surface *O atoms in the examples are more reactive, and their high spin state facilitates the breaking of CH bonds in ethanol, accelerating oxidation to carbon dioxide and water.
[0036] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent substitutions, and improvements made to the above embodiments without departing from the scope of the present invention, based on the technical essence of the present invention and within the spirit and principles of the present invention, shall still fall within the protection scope of the present invention.
Claims
1. A method for preparing iridium-doped indium oxide material in an atomically advanced transition metal iridium-doped indium oxide ethanol gas sensor, characterized in that, The preparation method of iridium-doped indium oxide material is as follows: Step 1: Weigh out indium nitrate; Step 2: Dissolve indium nitrate in a mixed solution of deionized water and ethanol, stir continuously and add ammonia water to obtain a suspension; Step 3: Stir the suspension obtained in Step 2 under heating conditions; Step 4: After washing and drying the white solid obtained from the reaction, transfer it to a muffle furnace for calcination to obtain indium oxide solid powder; Step 5: Weigh out indium oxide and chloroiridium acid for later use; the mass ratio of indium oxide to chloroiridium acid is 1:(0.1~1). Step 6: Dissolve the weighed indium oxide and chloroiridic acid in deionized water and stir under heating conditions; the heating temperature is 10~150℃ and the stirring time is not less than 10 h; Step 7: After washing and drying the white solid obtained from the reaction, transfer it to a muffle furnace for calcination to obtain iridium-doped indium oxide solid powder; the working temperature of the muffle furnace is 200 ℃~500 ℃, the working time is not less than 3 h, and the heating rate is 2~10 ℃ / min.
2. The method for preparing iridium-doped indium oxide material in an atomically advanced transition metal iridium-doped indium oxide ethanol gas sensor according to claim 1, characterized in that, The mass of indium nitrate weighed in step 1 is 5~15g.
3. The method for preparing iridium-doped indium oxide material in an atomically advanced transition metal iridium-doped indium oxide ethanol gas sensor according to claim 1, characterized in that, In step 4, the working temperature of the muffle furnace is 400 ℃~600 ℃, the working time is not less than 1 h, and the heating rate is 2~10 ℃ / min.